Emigration flows from North Africa to Europe. - (:unkn) unknown (My University, 2014)
The region of North Africa (NA) represents a striking locality regarding migration with several migration patterns, namely emigration in the form of labour export to Europe and North America and, to a lesser extent, to the Arab Gulf area. The latter has increased enormously in the last decade because of the political instability in most of the NA countries. The aim of the present chapter was to explore the patterns of migration stocks and flows in NA countries, based on several websites, systematic review of journals, comparable data available by the United Nations and by the International Organization of Migration. The NA region has become an area of transit migration and labour migration. Emigrant flows from NA countries towards Europe and North America are increasing this decade more than towards the Arab Gulf countries after being replaced by Asian labour. The recent increase in the proportion of women among the migrant population is remarkable. Remittances sent by African migrants have become an important source of external finance for countries of origin. Transient and irregular migration to Egypt originates at the borders with Sudan, Palestine and Libya with destination to the Euro Mediterranean countries. In Tunisia and Morocco, irregular migrants originate from Sub-Saharan Africa to the northern borders. The NA countries serve as departure rather than destination countries, and migration flows to the Euro-Mediterranean countries through legal or illegal routes.
Keywords: African Research